The Effect of Warm Water Foot Soak Therapy on Blood Pressure in Patients with Hypertension - Aknes Monita Sari; Ika Silvitasari (OVUM : Journal of Midwifery and Health Sciences, 2026)
Hypertension is a major global health problem and increases the risk of cardiovascular, renal, and cerebrovascular diseases if not properly managed. This study aimed to determine the effect of warm water foot soak therapy on blood pressure in patients with hypertension. This study used a pre-experimental one-group pre-test and post-test design. A total of 30 respondents were selected using purposive sampling. The intervention was administered for 15 minutes for five consecutive days using water at a temperature of 39–42°C. Blood pressure was measured before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test. The results showed a significant decrease in systolic and diastolic blood pressure after the intervention (p = 0.000). Warm water foot soak therapy is effective as a complementary non-pharmacological intervention for controlling blood pressure in patients with hypertension.